The Epistemological Place of Nursing as Art from an Aristotelian Viewpoint [O Lugar Epistemológico Da Enfermagem Como Arte Desde Uma Perspectiva Aristotélica] [el Lugar Epistemológico de la Enfermería Como Arte Desde Una Mirada Aristotélica] - Pavez-Lizarraga, A; Castillo-Lobos, L (Universidad de Alicante, 2021)
Nursing is the science of caring which sustains its knowledge on a complex theoretical corpus. In its evolution as a science, four epistemological dimensions are identified belonging to the knowledge of Nursing: the complexity of the discipline, the paradigmatic changes of science, the coexistence of quantitative-qualitative paradigms, and the gender perspective. During the 19th and 20th centuries, conceptualizing Nursing as a whole that involves science and art represented a contradictory reality that went beyond the development of modern science by putting together the field of knowledge of the natural sciences with that of the social sciences and art. This abject convergence of health science is vanguardist and precursor of the integration of the quantitative-qualitative paradigms to understand the diversity of the expressions of human health. Attend to the care needs supported by a theoretical body that understands the health phenomenon, rescuing the aesthetic, creative and individual principles of care, makes Nursing a transgressive science and, from an Aristotelian point of view, represents in itself a poeisis, inasmuch as its reflection and practice constitute the creation of unique, individual, complex and aesthetic care that demands biological, socio-psycho-cultural and spiritual coherence. © en Estudios Americanos mención Estudios Políticos y Sociales.